2023
DOI: 10.3389/fmicb.2023.1207441
|View full text |Cite
|
Sign up to set email alerts
|

Role of efflux pumps, their inhibitors, and regulators in colistin resistance

Abstract: Colistin is highly promising against multidrug-resistant and extensively drug-resistant bacteria clinically. Bacteria are resistant to colistin mainly through mcr and chromosome-mediated lipopolysaccharide (LPS) synthesis-related locus variation. However, the current understanding cannot fully explain the resistance mechanism in mcr-negative colistin-resistant strains. Significantly, the contribution of efflux pumps to colistin resistance remains to be clarified. This review aims to discuss the contribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 141 publications
0
1
0
Order By: Relevance
“…CCCP was then used as an efflux pump inhibitor to confirm efflux pump activity in colistin resistance isolates. 26 The MIC of CCCP was evaluated by broth microdilution method ranging from 128 to 0.5 μg mL −1 . The 1/2MIC of CCCP was used to investigate the presence of an efflux pump.…”
Section: Methodsmentioning
confidence: 99%
“…CCCP was then used as an efflux pump inhibitor to confirm efflux pump activity in colistin resistance isolates. 26 The MIC of CCCP was evaluated by broth microdilution method ranging from 128 to 0.5 μg mL −1 . The 1/2MIC of CCCP was used to investigate the presence of an efflux pump.…”
Section: Methodsmentioning
confidence: 99%
“…Addition of L-Ara4N and/or PEtn to lipidA changes the negative charge of the cell membrane by neutralizing the negatively charged phospholipids [47][48][49][50]. In detail, the addition of PEtn to the 1′-or 4′-phosphate group of lipid A is carried out by PmrC, a putative membrane protein with phosphoethanolamine transferase activity encoded by pmrABC operon [11,[51][52][53][54].…”
Section: Modification Of Lps Structure By Chromosomal Mutationsmentioning
confidence: 99%
“…Further evidence for the role of efflux pumps in colistin resistance is the suppression of resistance by efflux pump inhibitor (EPI), cyanide-3-chlorophenylhydrazone (CCCP) in A. baumannii, P. aeruginosa, K. pneumoniae, and S. maltophilia [118]. However, a possible explanation is that CCCPmediated depolarization of the electrochemical gradient may restore the negative charge of the outer membrane and lead to increased susceptibility to colistin [48,118]. Furthermore, various studies suggested a complex regulatory relationship between the efflux pumps and their transcriptional regulators and LPS synthesis, transport, and modification [48].…”
Section: Overexpression Of Efflux Pumpsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of L-Ara4N and/or PEtn to lipidA changes the negative charge of the cell membrane by neutralizing the negatively charged phospholipids [47][48][49][50]. In detail, the addition of PEtn to the 1′-or 4′-phosphate group of lipid A is carried out by PmrC, a putative membrane protein with phosphoethanolamine transferase activity encoded by pmrABC operons [11,[51][52][53][54].…”
Section: Modification Of Lps Structure By Chromosomal Mutationsmentioning
confidence: 99%